(untitled) (International Journal of Engineering and Computer Science, 2018)
Wheelchairs are used by the people who cannot walk due to physiological or physical illness, injury or any disability. Recent development promises a wide scope in developing smart wheelchairs. The present article presents a gesture based wheelchair which controls the wheelchair using hand movements. The system is divided into two main units: Mems Sensor and wheelchair control. The Mems sensor, which is connected to hand, is an 3-axis accelerometer with digital output (I2C) that provides hand gesture detection, converts it into the 6- bit digital values and gives it to the PIC controller. The wheelchair control unit is a wireless unit that is developed using other controller.